2019
DOI: 10.1002/celc.201901687
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Liquid Solutions on the Ionic Conductivity of Li1.3Al0.3Ti1.7(PO4)3 Solid Electrolytes

Abstract: Hydrothermal synthesis is used to successfully prepare Li1.3Al0.3Ti1.7(PO4)3 (LATP) solid electrolytes with high lithium‐ion conductivity, typically being 0.213 mS cm−1. The best calcination and sintering temperatures are optimized to be 900 and 1075 °C, respectively. The solvent effects on conductivity and microstructure of LATP in water, ethanol and acetone are investigated by using impedance spectroscopy and scanning electron microscopy. The conductivity of LATP in water reaches 1.167 mS cm−1. In ethanol, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The weight loss of the CPEs was, however, much lower than those of the pure PVA and PVA/PAN blend membranes, reflecting the ultrahigh decomposition temperature of the LATP filler (1100 °C). 60 The thermal stability of the PVA/PAN/LITFSI/LATP/SN membrane was evaluated by testing in an oven at 150 °C for 3 h. The PE separator was also tested for comparison. As shown in Figure S3, the shape and dimension of the PVA/PAN/ LITFSI/LATP/SN (CPE) membrane still remained well after a 3 h test with a very low shrinkage.…”
Section: Methodsmentioning
confidence: 99%
“…The weight loss of the CPEs was, however, much lower than those of the pure PVA and PVA/PAN blend membranes, reflecting the ultrahigh decomposition temperature of the LATP filler (1100 °C). 60 The thermal stability of the PVA/PAN/LITFSI/LATP/SN membrane was evaluated by testing in an oven at 150 °C for 3 h. The PE separator was also tested for comparison. As shown in Figure S3, the shape and dimension of the PVA/PAN/ LITFSI/LATP/SN (CPE) membrane still remained well after a 3 h test with a very low shrinkage.…”
Section: Methodsmentioning
confidence: 99%
“…Sodium zirconium phosphate (NaZr 2 (PO 4 ) 3 (NZP) is the parent compound of the Na-based super ionic conductor named NASICON [ 359 , 360 , 361 , 362 , 363 , 364 , 365 , 366 , 367 , 368 , 369 , 370 , 371 , 372 , 373 , 374 , 375 , 376 , 377 , 378 , 379 , 380 , 381 , 382 , 383 , 384 , 385 , 386 , 387 , 388 , 389 , 390 , 391 , 392 , 393 , 394 , 395 , 396 , 397 , 398 , 399 , 400 , 401 , 402 , 403 , 404 , 405 , 406 ,…”
Section: Oxide Solid Electrolytesmentioning
confidence: 99%
“…Recently, Case et al [ 384 ] performed computational studies of LATP and Binninger et al [ 276 ] analyzed the electrochemical stability window of the LATP electrolyte using computational methods. Furthermore, Siyal et al [ 385 ] analyzed a gel polymer electrolyte with 15 wt.% LATP composite, and few other researchers studied bare and LATP composite electrodes [ 379 , 386 , 387 , 388 ]. Yen et al [ 389 ] characterized LATP powders prepared by hydrothermal synthesis followed by calcination (900–1100 °C), cold pressing (90 MPa), and post sintering, which exhibit ionic conductivity of grain and grain boundary of 6.57 × 10 −4 and 4.59 × 10 −4 S cm −1 , respectively.…”
Section: Oxide Solid Electrolytesmentioning
confidence: 99%
“…It should be noted that synthesis conditions have a strong influence on the electrochemical performance of hydrothermally produced LATP. [124] For example, after exploring a series of parameters, Kim et al found that the optimum hydrothermal reaction time for the synthesis of [114] Copyright 2006, Elsevier. b) XRD patterns of a-LATP (x = 0.3) powder obtained by mechanical milling treatment (top) and c-LATP (x = 0.3) powder obtained by heat treatment of a-LATP (x = 0.3) powder (bottom).…”
Section: Hydrothermal Synthesis Methodsmentioning
confidence: 99%